The Impact of Maternal Nutrition Status on Maternal and Fetal Outcomes: A Prospective Observational Study - Shipra Singh; Vinita Gupta; Seema Rawal; Sachin Parmar; Soumitra Sethia; Ranjana Sharma (Journal of Pharmacy and Bioallied Sciences)
Background: Maternal body mass index (BMI) significantly influences both maternal and fetal outcomes. Changing socioeconomic factors in India have led to a rise in both obesity due to lifestyle factors and malnutrition due to poverty. Each extreme of BMI—underweight and overweight—has distinct risks. Overweight and obese women face complications, such as gestational diabetes, gestational hypertension, and macrosomia, while underweight women are at higher risk of conditions, like intrauterine growth restriction (IUGR), low birth weight, and anemia. Materials and Methods: This observational study was conducted over nine months from September 2019 to June 2020, involving 850 pregnant women attending the gynecology outpatient department (OPD) at a tertiary hospital. First-trimester BMI was calculated to classify patients as underweight (<18.5), normal weight (18.5–22.9), overweight (23–24.9), pre-obese (25–29.9), or obese (≥30). Data collection included personal and medical history, physical and obstetric examinations, and monitoring of maternal and fetal outcomes. Results: The study found that women at the extremes of BMI experienced higher rates of adverse outcomes. Obese and overweight women showed increased risks of gestational diabetes, hypertension, preeclampsia, cesarean deliveries, and postpartum hemorrhage. Conversely, underweight women had a higher incidence of IUGR, anemia, preterm birth, and increased perinatal mortality. Conclusion: Both high and low maternal BMI are associated with distinct risks for adverse pregnancy outcomes. Preconception counseling and lifestyle guidance for women of reproductive age may reduce the incidence of these complications, emphasizing the importance of optimal weight management for improved maternal and fetal health outcomes.